Finding Ashley [compact disc, unabridged] - Steel, Danielle (Recorded Books, Inc., 2021)
Two brave women, estranged sisters, get the chance to connect and right the wrongs of the past, turning wrenching loss into reconnection and a family reunited after bringing dark secrets into the light.